Pengembangan Pasar Tradisional Mattirowalie Berbasis Arsitektur Berkelanjutan di Kabupaten Barru - Asrar, Muhammad; Herniwati, Andi; Oktawati, A. Eka (TIMPALAJA : Architecture Student Journals, 2025)
Although traditional markets are vital public venues for social, commercial, and cultural activity, they frequently suffer a number of difficulties that make patrons uncomfortable. The Mattirowalie Traditional Market, a commercial market in Barru Regency, has poor facilities and management problems that make shopping there less enjoyable. In order to redesign the Mattirowalie Traditional Market, this study will employ a sustainable architecture strategy that strikes a balance between social, economic, and environmental factors. In addition to case studies of comparable markets, the research involves interviews with users and market administrators. Enhancing user comfort, boosting local economic growth, and promoting sustainability are the anticipated results..